Konsep Keadilan Poligami dalam Al-Qur'an: Tafsir Maudhu'i Studi Tafsir Maudhu'i atas Surah an-Nisa' Ayat 3 dan 129 - Via Fadhilah; Muhammad Yusuf Siddik; Ahmad Farhan; Setyawan Setyawan (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This article examines the concept of justice in polygamy in the Qur'an through a thematic study of Surah an-Nisa' verses 3 and 129. The study is motivated by the fact that justice, as the central condition for the permissibility of polygamy, is often understood narrowly or implemented inconsistently in Muslim family life. Using descriptive qualitative library research, this article analyzes Qur'anic verses, asbab al-nuzul, linguistic meanings, classical and contemporary tafsir, hadith, Islamic legal sources, and relevant scholarly literature. The findings show that Qur'anic justice in polygamy consists of external or material justice, which is obligatory and includes fair distribution of maintenance, residence, time, and treatment, and internal or affective justice, which lies beyond complete human control. Although emotional equality cannot be fully achieved, a husband must control personal inclination so that it does not result in neglect, discrimination, or psychological harm. The integration of verses 3 and 129 indicates that polygamy is not an unrestricted command, but a conditional legal concession directed toward preventing injustice and preserving family harmony.